Emerging Infectious Diseases and the Role of Syndromic Surveillance in the Developing World - Catherine Zatorski (Journal of Medical Bacteriology, 2015)
Despite  impressive  advancements  in  diagnostic  and  treatment technologies,  infectious  diseases  still  cause  a  significant  amount  of mortality and morbidity throughout the world due to the unpredictable and inevitable  rise  of  new  or  previously  dormant  pathogens.  Emerging infectious disease (EID) outbreaks are mainly associated with changes in physical environment and human behavioral activities, and disproportionately affect developing countries. Syndromic surveillance, while challenged in developing countries by inadequate communication and public health infrastructure, could build on pre-existing systems to complement  existing governmental  and  non-governmental  programs  for outbreak detection and offers a promising avenue to detect EID eventsearlier in the course of an outbreak.